Relative frequency and conditional probability based associated dynamic features in extended haptic accuracy - Chul-wook Park; Hyeongsaeng Park (Korea Institute of Sport Science, 2020)
Purpose This study measured the haptic extroperception accuracy, that is, judging one hit position in a hand-held object. Especially, what factors associated the estimation of contact position when the impact is made at the grasped implement by hitting the ball. Methods Relative frequency and conditional probability based analysis verified that perceivers influenced not only the amount of pressure distinguished impressions by the coefficient of restitution but also the pressure distributions encoded impressions by the distance from the hand to the impact. Results Results conformed to previous invariant characteristic on dynamic touch in showing that perceiving the location of the impact of grasped objects, including dominant perceiving selectively modality, is constrained by inertial properties with such success requires appreciating the location of the implement's center of percussion. Conclusion Investigated in this planes captured as a mechanical factor, we would suggest a broader hypothesis for further research into the effects of the rotational inertia related to haptic position accuracy in the hand-held object, and leading to different estimates of system function providing an account of generalization that accommodates of its varied aspects.